Status and epidemiological characteristics of high-risk human papillomavirus infection in multiple centers in Shenyang - Yang, Di; Zhang, Jing; Cui, Xiaoli; Ma, Jian; Wang, Chunyan; Piao, Haozhe (Frontiers in Microbiology, 2022)
Human papillomavirus (HPV) causes warts in various parts of the body, depending on the strain. Since the status and genotype distribution of HPV infection in women in Shenyang remain unknown, in this study, we sought to reveal the epidemiological characteristics of high-risk HPV (HR-HPV) infection in women in Shenyang, the current situation of HPV infection in Shenyang, and to provide a theoretical basis for the prevention and treatment of cervical cancer. From December 2018 to December 2021, 6,432 urban and rural women from the Liaoning Cancer Hospital and the Sujiatun Women and Infants’ Hospital were selected for Thinprep cytology test (TCT) and HR-HPV detection. Of the 5,961 women enrolled, 739 were HPV positive (12.40 %) and 562 were TCT positive (9.43 %). Statistical analyses showed the following HPV infected risk factors: high school ages and below (OR = 1.426 (1.199–1.696), p < 0.001), initial sexual life age ≤ 19 years (OR = 1.496 (1.008–2.220), p = 0.046), number of sexual partners > 1 (OR = 1.382 (1.081–1.768), p = 0.010), atypical squamous cells of undetermined significance (ASCUS) and above (OR = 10.788 (8.912– 13.060), p < 0.001), non-condom contraception (OR = 1.437 (1.103–1.871), p = 0.007), nationalities other than Han nationality (OR = 1.690 (1.187–2.406), p = 0.004), rural population (OR = 1.210 (1.031–1.419), p = 0.020). Compared to the HPV infection rate of women aged 56–65, the rate in women aged 35–45 (OR = 0.687 (0.549–0.860), p = 0.001) and 46–55 (OR = 0.740 (0.622–0.879), p = 0.001) decreased significantly. To conclude, risk factors of HPV infection among female patients include high school age and below, initial sexual life age ≤ 19 years, number of sexual partners > 1, ASCUS and above, non-condom contraception, nationalities other than Han nationality and rural population. This study provides a new basis for the prevention and treatment of cervical cancer.